Perancangan Pengalaman Pengguna Aplikasi Survei Online Berbayar Antar Mahasiswa berbasis Mobile menggunakan Metode Design Thinking - Nur Fajri Hayyuni Maulidya; Herman Tolle; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Student colleges as civitas academica have duty to research and develop, it could be homework, contest, until thesis. To get the data as research and development material, student colleges usually do surveys. The main problem in doing surveys is the low response rate in data collection. Based on Green Book data, the reason respondents participated in the survey is 36.6% because of the reward provided by the surveyor and 8.9% participants found an interesting survey. However, only a few surveyors that give reward to the respondents and the distribution of the survey is less widespread and centered becomes an obstacle for respondents to find interesting surveys. This research intends to design user experience for place the student colleges in spread the surveys as wide and centered so that it can facilitate in getting much and matching criteria respondents with give worth reward to them. The Design Thinking method used because focuses on user experience and is very effective at solving complex problems. In the testing stage, the researcher did the usability tests with the results of the effectiveness aspect of 91.25%, the efficiency aspect with an overall relative efficiency of 100% and with a time based efficiency of 0.034 goals/sec, and the satisfaction aspect of 74.5%. Beside that, the researcher did the user experience test to be measured by User Experience Questionnaire with the results of the Attractiveness, Stimulation, and Novelty aspects getting the Excellent category, while the Efficiency and Dependability aspects got the good category, and the Perspicuity aspect got the Above Average category.